Ultrasound-Targeted Microbubble Destruction Improves the Migration and Homing of Mesenchymal Stem Cells after Myocardial Infarction by Upregulating SDF-1/CXCR4: A Pilot Study - Lu Li; Shengzheng Wu; Zheng Liu; Zhongxiong Zhuo; Kaibin Tan; Hongmei Xia; Lisha Zhuo; Xiaojun Deng; Yunhua Gao; Yali Xu (Stem Cells International)
Mesenchymal stem cell (MSC) therapy shows considerable promise for the treatment of myocardial infarction (MI). However, the inefficient migration and homing of MSCs after systemic infusion have limited their therapeutic applications. Ultrasound-targeted microbubble destruction (UTMD) has proven to be promising to improve the homing of MSCs to the ischemic myocardium, but the concrete mechanism remains unclear. We hypothesize that UTMD promotes MSC homing by upregulating SDF-1/CXCR4, and this study was aimed at exploring this potential mechanism. We analyzed SDF-1/CXCR4 expression after UTMD treatment in vitro and in vivo and counted the number of homing MSCs in MI areas. The in vitro results demonstrated that UTMD not only led to elevated secretion of SDF-1 but also resulted in an increased proportion of MSCs that expressed surface CXCR4. The in vivo findings show an increase in the number of homing MSCs and higher expression of SDF-1/CXCR4 in the UTMD combined with MSCs infusion group compared to other groups. In conclusion, UTMD can increase SDF-1 expression in the ischemic myocardium and upregulate the expression of surface CXCR4 on MSCs, which provides a molecular mechanism for the homing of MSCs assisted by UTMD via SDF-1/CXCR4 axis.